2020
DOI: 10.3390/ijms21197245
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 Regulates Dlk1 Expression in Adipogenesis

Abstract: The tripartite motif-containing protein 28 (TRIM28) is a transcription corepressor, interacting with histone deacetylase and methyltransferase complexes. TRIM28 is a crucial regulator in development and differentiation. We would like to investigate its function and regulation in adipogenesis. Knockdown of Trim28 by transducing lentivirus-carrying shRNAs impairs the differentiation of 3T3-L1 preadipocytes, demonstrated by morphological observation and gene expression analysis. To understand the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
7
1
Order By: Relevance
“…5). However, we did not observe significantly decreased DNAm in the ART placentas compared to controls, which indicated that the ICR hypomethylation is not the only mechanism which affects the complex DLK1 regulation 59,60 .…”
Section: Art-and Subfertility-associated Placental Imprintingcontrasting
confidence: 73%
“…5). However, we did not observe significantly decreased DNAm in the ART placentas compared to controls, which indicated that the ICR hypomethylation is not the only mechanism which affects the complex DLK1 regulation 59,60 .…”
Section: Art-and Subfertility-associated Placental Imprintingcontrasting
confidence: 73%
“…First, it inhibits NLRP3 inflammasome activation and reduces reactive oxygen species production when overexpressed. 32 Second, TRIM30α, an isoform, can inhibit inflammatory responses by promoting the degradation of transforming growth factor-β-activated kinase 1 (TAK1)-binding protein 2 (TAB2) and TAB3, as well as a feedback loop of NF-κB activation, through the Toll-like receptor signalling pathway. 36 Overall, these two TRIM proteins can affect adipocyte formation and insulin sensitivity through regulation of target proteins, transcription factor expression, and epigenetics.…”
Section: Obesitymentioning
confidence: 99%
“…TRIM28 is a transcriptional regulator in adipocytes associated with increased fat mass 90 . It can be recruited by the transcription factor E2f1 to regulate the histone methylation of the delta‐like noncanonical notch ligand 1 (Dlk1; an adipogenic inhibitor) promoter, negatively regulating Dlk1 expression and promoting adipocyte differentiation 32 . TRIM28 also reduces the expression of Krüppel‐like factor (KLF) transcription factor 14, a well‐defined gender‐specific regulator, which in turn alters adiposity and body weight 91 .…”
Section: Mechanisms Of Trim Proteins In Other Insulin Resistance‐rela...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that KLF6 binding with histone deacetylase 3 to the DLK1 promoter (between −78 and −53 bp upstream of the transcriptional start site) results in DLK1 repression [47]. Contrarily, the E2F Transcription Factor 1 has been shown to activate the DLK1 promoter, and its activity is inhibited by a tripartite motif-containing protein 28 [48]. Finally, at the proximal 5 enhancer region, the DLK1 gene includes three putative hypoxia responsive elements at −758, −402, and −248 bp, and consequently its expression is induced by hypoxia inducible factor 1α (HIF-1α) and HIF-2α [49].…”
Section: Biological Functions Of Pttg1mentioning
confidence: 99%